Monitoring and Evaluation of 2015 Devrek Zonguldak Landslide within the scope of Flood Risk Assessment by Landsat-8 Satellite Data - Şerife Pınar Güvel; Mehmet Ali Akgül; Mehveş Feyza Akkoyunlu (Doğal Afetler ve Çevre Dergisi)
The mass movement towards stream beds and their accumulation there may cause flood events as a result of landslide events. In this study, Devrek Landslide, which occurred in 2015, was investigated by using a remote sensing technique. The Çomaklar stream is located at the lower elevations of this landslide region. Çomaklar stream and surrounding settlements are at risk of flooding due to the probability of preventing the water flow in the stream because of the effects of the landslide. Devrek district is located in Zonguldak in the northern part of Turkey. LANDSAT-8 satellite images between the dates 27 January 2015 and 22 July 2015 were used to investigate the location and size of the Devrek district landslide. Satellite-derived remote sensing data have been widely used in recent years to monitor changes on the earth's surface and to provide information. In this study, the Spectral Angle Difference method was used to compare the images before and after the landslide event. A change detection analysis was conducted between pre-landslide and post-landslide images to investigate the area affected by the disaster. As a result, the landslide was determined as 1050 meters in length and 110 meters in width, and the landslide area was calculated as 10.87 ha.